Daddy Pig's old chair (London : Ladybird, 2017)
"Let's have a rummage sale," says Madame Gazelle. Peppa and her friends give some old toys. What can Daddy Pig give?
Keywords: (Fictitious character); Readers (Primary); Children's stories